NEW DESSERTS ARE IN CORRECTION OF DEFICIT OF IODINE AND SELENIUM IN FEED OF POPULATION - Бондаренко, Ксения; Корзун, Виталий; Антонюк, Ирина (Modern engineering and innovative technologies, 2017)
Raising of problem. The deficit of iodine is directly related to the feed, with insufficient content of iodic products. World and home experience certifies that the most effective and expedient event of cardinal decision of problem are development and adj